2014
DOI: 10.1242/dev.099432
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin heavy chain plays multiple roles in polarizing the Drosophila oocyte downstream of Bic-D

Abstract: Bicaudal-D (Bic-D), Egalitarian (Egl), microtubules and their motors form a transport machinery that localizes a remarkable diversity of mRNAs to specific cellular regions during oogenesis and embryogenesis. Bic-D family proteins also promote dynein-dependent transport of Golgi vesicles, lipid droplets, synaptic vesicles and nuclei. However, the transport of these different cargoes is still poorly understood. We searched for novel proteins that either mediate Bic-Ddependent transport processes or are transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 61 publications
4
37
0
Order By: Relevance
“…The function of Dynein in endocytic uptake likely involves efficient localization of the Clathrin complex at the oocyte cortex ( Figure 10M). This is consistent with recent findings of Vazquez-Pianzola et al who demonstrated a role for the Dynein adaptor BicD in the cortical localization of Chc (Vazquez-Pianzola et al 2014).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The function of Dynein in endocytic uptake likely involves efficient localization of the Clathrin complex at the oocyte cortex ( Figure 10M). This is consistent with recent findings of Vazquez-Pianzola et al who demonstrated a role for the Dynein adaptor BicD in the cortical localization of Chc (Vazquez-Pianzola et al 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with published results, Clathrin heavy chain (Chc), Rab5, and Rab7 localized along the cortex in control oocytes ( Figure 2Q; data not shown) (Tanaka and Nakamura 2008;Vazquez-Pianzola et al 2014). In egg chambers expressing dmn shRNA-A, two phenotypes were observed.…”
Section: Dmn Depletion Phenotypessupporting
confidence: 90%
See 1 more Smart Citation
“…grk mRNA, and to a lesser extent, osk mRNA, were also enriched in Egl pellets ( Figure 1D). Thus, as observed in Drosophila embryos (Dienstbier et al 2009;Vazquez-Pianzola et al 2014), Egl associates with mRNAs that are destined for localization.…”
Section: Resultsmentioning
confidence: 68%
“…In Drosophila egg chambers, apart from its role in the formation of clathrincoated vesicles, Chc has been reported to play a role in the polarization of the microtubule network at stage 6. 54 Clc has been shown to direct endocytosis by providing direction for membrane internalization. 55 After stage 7, Drongo localizes mainly at the oocyte's cortex, where it shows significant overlap with Clc-GFP, concurrent with the activation of bulk endocytosis.…”
Section: Drongo Protein Is Associated With Clathrin F-actin and Arf51fmentioning
confidence: 99%